2007
DOI: 10.1038/sj.onc.1210533
|View full text |Cite
|
Sign up to set email alerts
|

Endoglin inhibits prostate cancer motility via activation of the ALK2-Smad1 pathway

Abstract: Endoglin is a transforming growth factor b (TGFb) superfamily auxiliary receptor. We had previously shown that it suppressed prostate cancer (PCa) cell motility, and that its expression was lost during PCa progression. The mechanism by which endoglin inhibits PCa cell motility is unknown. Here we demonstrate that endoglin abrogates TGFb-mediated cell motility, but does not alter cell surface binding of TGFb. By measuring Smad-specific phosphorylation and Smad-responsive promoter activity, endoglin was shown to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
85
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(100 citation statements)
references
References 34 publications
(44 reference statements)
13
85
2
Order By: Relevance
“…In both the MCF10A.ErbB2 and MDA-MB-231 cells, expression of endoglin attenuates the promigratory/invasive activities of TGF-b but has no effect on TGF-b-mediated Smad2/3 or Smad1/5/8 signaling. Previously it has been reported that endoglin can inhibit TGF-b-mediated migration and invasion of prostate-cancer cell lines (Craft et al, 2007;Romero et al, 2010) and transformed mouse keratinocytes (Perez-Gomez et al, 2007). Consistent with our findings, endoglin had no effect on TGF-b-mediated Smad activation in the prostate cancer cells.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In both the MCF10A.ErbB2 and MDA-MB-231 cells, expression of endoglin attenuates the promigratory/invasive activities of TGF-b but has no effect on TGF-b-mediated Smad2/3 or Smad1/5/8 signaling. Previously it has been reported that endoglin can inhibit TGF-b-mediated migration and invasion of prostate-cancer cell lines (Craft et al, 2007;Romero et al, 2010) and transformed mouse keratinocytes (Perez-Gomez et al, 2007). Consistent with our findings, endoglin had no effect on TGF-b-mediated Smad activation in the prostate cancer cells.…”
Section: Discussionsupporting
confidence: 91%
“…From an initial demethylation screen, we identified ENG as a candidate gene for epigenetic regulation in breast cancer cell lines. Together with previous reports that endoglin can inhibit the migration of other epithelial tumors (Craft et al, 2007;Perez-Gomez et al, 2007), we hypothesized that expression of endoglin might function to suppress breast cancer progression. To address this we investigated the functional role of endoglin in both in vitro and in vivo models, its impact on the TGF-b signaling pathway and the prognostic impact and regulation of endoglin expression in a large cohort of invasive breast cancers.…”
Section: Introductionmentioning
confidence: 68%
“…More recent data have shown that decreased Endoglin levels in prostate cancer cells result in increased metastasis and increased tumour size (18). The inhibition of prostate cell migration by Endoglin occurs through the activation of TGF-β co-receptor signalling and the consequent phosphorylation of Smad1, as well as through a Smad1-independent pathway (19,20).…”
Section: Introductionmentioning
confidence: 99%
“…Downregulation of ENG in esophageal cancer in this study may provoke cancer progression through blocking the tumor suppression of the TGF-signaling cascade. For the functional impact of ENG in cell migration, ENG may suppress cancer cell motility by a TGF--dependent mechanism involving activation of the type I TGF-receptor and Smad1, as reported in the study of prostate cancer cells (Craft et al 2007). In endothelial cells, high endoglin expression stimulates the type I activin receptor-like kinases (ALK1) pathway and indirectly inhibits ALK5 signaling for endothelial cell proliferation and migration, thus promoting the state of angiogenesis.…”
Section: Eng (Endoglin)mentioning
confidence: 98%